If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + -10w + -3 + 2 = 20 Reorder the terms: -3 + 2 + 3w + -10w = 20 Combine like terms: -3 + 2 = -1 -1 + 3w + -10w = 20 Combine like terms: 3w + -10w = -7w -1 + -7w = 20 Solving -1 + -7w = 20 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -7w = 20 + 1 Combine like terms: -1 + 1 = 0 0 + -7w = 20 + 1 -7w = 20 + 1 Combine like terms: 20 + 1 = 21 -7w = 21 Divide each side by '-7'. w = -3 Simplifying w = -3
| 47=7x+6(-1x+6) | | -48=4x+3(-4x+8) | | 74=3x+2(6x-8) | | 81=-2x-3(5x+7) | | x^2-36a^2+20x+100=0 | | -110=-2x+7(3x+6) | | 3(2x-1)-2=2(x+9)+1 | | x^2-16y^3=0 | | 23*3=23 | | 35+8x=7x+3 | | 2x(3x-4)+5=3x(2x-5)-4 | | 3a-2=2-2a+1 | | h=-16t^2+8t+80 | | H(t)=16t^2+144 | | -4x^2+22x+42=0 | | (2x-1)(2x-1)-25=0 | | (x-6)(x-6)-16=0 | | 3.5s=-38.5 | | k+2*k^2-15=0 | | r+4*r^2-5=0 | | -6x-2(-3x-1)(-3x-1)=0 | | (4x+3)(4x+3)-10=0 | | -5x^2-2x-2=0 | | 3.5*13= | | 3-(2x-4)=x+7 | | 7x-47=2 | | 3.5*13*1.5= | | (x)2+16x+64=0 | | (5x+2)(5x+2)-5=0 | | (4x+2)(4x+2)-36=0 | | 2x^2+x+4=0 | | 9x^2+6x-18=0 |